Is the social withdrawal subscale a valid instrument to assess social withdrawal among colorectal cancer survivors with permanent stomas? A validation study - Guopeng Li; Xudong He; Qi Yao; Xiaoling Dong (BMC Psychiatry)
Abstract Background Although social withdrawal is common among colorectal cancer (CRC) survivors with permanent stomas, it has been poorly addressed due to a lack of valid assessment tools. The social withdrawal subscale (SWS) from the Internalized Stigma of Mental Illness (ISMI) scale shows promise for assessing social withdrawal. However, there was no available data on its validity for this purpose. This study aimed to investigate the reliability and validity of the SWS as a screening tool for identifying survivors at risk of social withdrawal. Methods Two separate convenience samples of 127 and 245 CRC survivors with permanent stomas were selected. Item analysis and exploratory factor analysis (EFA) were conducted with the first sample of 127 survivors. Confirmatory factor analysis (CFA), reliability analysis, and tests for convergent and discriminant validity were performed with the second sample of 245 survivors. Additionally, the screening cut-off score and accuracy of the SWS scores were determined using receiver operating characteristic (ROC) curves. Results The item-total correlation coefficients of the SWS ranged from 0.530 to 0.787. The EFA demonstrated a single-factor structure for the SWS. The CFA confirmed appropriate construct validity (χ²/df = 103.115/52 = 1.983, goodness-of-fit index (GFI) = 0.925, comparative fit index (CFI) = 0.959, and root mean square error of approximation (RMSEA) = 0.068). The test–retest reliability was 0.849. Pearson correlation analysis showed significant and moderate to large relationships between the SWS and the chosen criterion measures, supporting its good convergent validity. ROC analysis identified SWS scores of ≥ 15 as the optimal screening cut-off, with a sensitivity of 86.5%, specificity of 50.5%, and an area under the curve (AUC) of 0.748 (95% CI: 0.673–0.823, P < 0.001). Conclusion The SWS demonstrates acceptable reliability and validity for measuring social withdrawal among CRC survivors with permanent stomas. Future studies should further evaluate its utility in clinical settings.